A nitrogen-sulfur co-doped carbon dot lubricating additive, a preparation method and application thereof
Patent Information
- Application Number
- CN202311399274.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-26
AI Technical Summary
但是,研究中仍存在一些问题,如制备流程复杂,无法大规模合成等,极大地限制了其在工业上的商业价值
[0019](1) By screening the structure and type of precursors, this invention can prepare carbon dots with passivated surfaces rich in polar groups such as oxygen, nitrogen, and sulfur, which can make them exhibit excellent dispersion stability and higher anti-wear and friction reduction properties in synthetic lubricating oils. The raw materials used in the preparation method are readily available, the synthesis cost is low, the operation method is simple, and the application range is wide. The nitrogen-sulfur co-doped carbon dot lubricating oil additive prepared by the preparation method of this invention has good dispersion stability and still maintains good lubrication performance after five months, exhibiting extremely long lubrication time.
Smart Images

Figure CN117448059B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lubricating oil additive technology, specifically relating to a nitrogen-sulfur co-doped carbon point lubricating additive, its preparation method, and its application. Background Technology
[0002] In large-scale machinery and transportation, energy losses due to friction and wear account for approximately 30% of global energy consumption. Lubrication is the most effective way to reduce wear. During the Industrial Revolution, the demand for lubricating oil has increased dramatically, with over 78% of the world's annual lubricating oil demand being met by mineral oil-based lubricants. However, the production and use of mineral oils are often accompanied by pollution and environmental problems. Advances in equipment technology have led to more stringent conditions and requirements for lubricants, many of which exceed the applicable scope of mineral oil-based lubricants, resulting in a continuous decline in their global usage. They are being replaced by alternatives such as polyalphaolefin (PAO), polyethylene glycol (PEG), and polyalkylene glycol (PAG). However, the performance of synthetic lubricants under long-term, high-speed, or high-load operation largely depends on the performance of lubricant additives. Carbon-based nanomaterials possess unique structural characteristics, which can impart physicochemical properties different from traditional materials, making them of significant application and development value. They show promising application prospects as synthetic lubricant additives.
[0003] However, due to the chemical inertness of nanoparticles and the complexity and high cost of dispersion media, it is difficult to ensure their long-term stable dispersion in lubricating oils. Therefore, improving their dispersion stability in lubricants is crucial for tribological properties. Carbon dots are a novel nanomaterial with a diameter of less than 10 nanometers, first reported in 2004. Their excellent fluorescence, chemical stability, and biocompatibility have led to their widespread application in biomedicine, bioimaging, and optoelectronic displays. Compared to traditional carbon materials, carbon dot surfaces offer greater designability. However, some challenges remain in research, such as complex preparation processes and the inability to synthesize on a large scale, which significantly limit their commercial value in industry. Summary of the Invention
[0004] The purpose of this invention is to address the limitations of complex synthetic lubricant preparation processes and industrial applications by providing a nitrogen-sulfur co-doped carbon dot lubricant additive, its preparation method, and its applications. This preparation method uses readily available raw materials, has low synthesis costs, is simple to operate, and has a wide range of applications. The nitrogen-sulfur co-doped carbon dot lubricant additive prepared using this invention exhibits good dispersion and lubrication stability in synthetic lubricants, and further enhances the load-carrying capacity and anti-wear / friction-reducing properties of synthetic lubricants.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows:
[0006] The first objective of this invention is to provide a method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive, comprising the following steps:
[0007] Trinitropyrene and thiourea were dissolved in water, and amine was added to form a mixed solution. The solution was then ultrasonically dispersed in a constant temperature water bath. After ultrasonic treatment, the precursor was obtained by hydrothermal treatment at 160-250℃.
[0008] An organic solvent was added to the precursor, and after mixing at room temperature, the mixture was filtered, dialyzed, and dried to obtain a nitrogen-sulfur co-doped carbon dot lubricating oil additive.
[0009] Preferably, in the mixed solution, the concentration of trinitropyrene is 1.0–8.0 g / L, and the concentration of thiourea is 0.1–1.0 M.
[0010] Preferably, when the amine is ammonium hydroxide, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 1.0–2.0 M; when the amine is one of guanidinopropionic acid, glutamic acid, histidine and its derivatives, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 0.1–0.3 M.
[0011] Preferably, the temperature of the constant temperature water bath is 10-30℃, and the ultrasonic dispersion time is 1-2 hours.
[0012] Preferably, the hydrothermal treatment time is 6 to 18 hours.
[0013] Preferably, the volume ratio of the precursor to the organic solvent is 1:1, and the organic solvent is one of ethanol, methanol, and ethylene glycol.
[0014] Preferably, the filter membrane used for vacuum filtration is a 0.22μm aqueous microporous filter membrane, and the dialysis bag used for dialysis has a molecular weight cutoff of 500-3500 Da, with a dialysis time of 1-2 days.
[0015] A second objective of this invention is to provide a nitrogen-sulfur co-doped carbon dot lubricant additive prepared by the above-described preparation method.
[0016] A third objective of this invention is to provide the application of the above-mentioned nitrogen-sulfur co-doped carbon dot lubricating oil additive in lubricating oil, wherein the amount of nitrogen-sulfur co-doped carbon dot added to the lubricating oil is 0.05 to 5 wt%.
[0017] Preferably, the lubricating oil is one of PEG, PAO, and PAG.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] (1) By screening the structure and type of precursors, this invention can prepare carbon dots with passivated surfaces rich in polar groups such as oxygen, nitrogen, and sulfur, which can make them exhibit excellent dispersion stability and higher anti-wear and friction reduction properties in synthetic lubricating oils. The raw materials used in the preparation method are readily available, the synthesis cost is low, the operation method is simple, and the application range is wide. The nitrogen-sulfur co-doped carbon dot lubricating oil additive prepared by the preparation method of this invention has good dispersion stability and still maintains good lubrication performance after five months, exhibiting extremely long lubrication time.
[0020] (2) The results showed that, compared with pure PEG200, a concentration of only 0.1wt% could reduce the average friction coefficient from 0.245 to 0.128, a reduction of 56%, and the wear volume could be reduced by 59%. Attached Figure Description
[0021] Figure 1 The image shows the TEM morphology of the carbon dots prepared in Example 1 of this invention.
[0022] Figure 2 The friction coefficient curve and wear scar surface morphology results of carbon dots prepared in Example 1 of the present invention with PEG200 concentration of 0.1wt% are shown. Figure 2 In the figure, 'a' is the friction coefficient curve of various doped carbon dot lubricants, and 'b' is the surface morphology of the wear scar after lubrication with various doped carbon dot lubricants and the surface morphology of the wear scar after lubrication with pure PEG200.
[0023] Figure 3 The images show the dispersion stability of carbon dots prepared in Example 1 of this invention in PEG200 and a comparison of their tribological properties before and after placement. Figure 3 In the figure, a is a photograph of N,S@CDs dispersed in PEG200 at different storage times (5 months), b is a particle size distribution of N,S@CDs in PEG200 after 5 months, and c is a comparison of the tribological properties of freshly prepared N,S@CDs and N,S@CDs after 5 months of storage. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0026] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0027] Trinitropyrene and thiourea were dissolved in water, and amine was added to form a mixed solution. The solution was then ultrasonically dispersed in a constant temperature water bath. After ultrasonic treatment, the precursor was obtained by hydrothermal treatment at 160-250℃.
[0028] An organic solvent was added to the precursor, and after mixing at room temperature, the mixture was filtered, dialyzed, and dried to obtain a nitrogen-sulfur co-doped carbon dot lubricating oil additive.
[0029] This invention, by screening the structure and type of precursors, can prepare carbon dots with passivated surfaces rich in polar groups such as oxygen, nitrogen, and sulfur. This allows them to exhibit excellent dispersion stability and higher anti-wear and friction-reducing properties in synthetic lubricating oils. The raw materials used in the preparation method are readily available, the synthesis cost is low, the operation method is simple, and the application range is wide. The nitrogen-sulfur co-doped carbon dot lubricating oil additive prepared using the preparation method of this invention has good dispersion stability and maintains good lubrication performance even after five months, exhibiting extremely long lubrication duration.
[0030] In one specific embodiment, the concentration of trinitropyrene in the mixed solution is 1.0–8.0 g / L, and the concentration of thiourea is 0.1–1.0 M.
[0031] In one specific embodiment, when the amine is ammonium hydroxide, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 1.0–2.0 M; when the amine is one of guanidinopropionic acid, glutamic acid, histidine, or their derivatives, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 0.1–0.3 M.
[0032] In one specific embodiment, the temperature of the constant temperature water bath is 10–30°C, and the ultrasonic dispersion time is 1–2 hours.
[0033] In one specific embodiment, the hydrothermal treatment time is 6 to 18 hours.
[0034] In one specific embodiment, the volume ratio of the precursor to the organic solvent is 1:1, and the organic solvent is one of ethanol, methanol, and ethylene glycol.
[0035] In one specific embodiment, the filter membrane used for vacuum filtration is a 0.22 μm aqueous microporous filter membrane, and the dialysis bag used for dialysis has a molecular weight cutoff of 500–3500 Da, with a dialysis time of 1–2 days.
[0036] The nitrogen-sulfur co-doped carbon dot lubricant additive prepared by the above method.
[0037] The above-mentioned nitrogen-sulfur co-doped carbon dot lubricating oil additive is used in lubricating oil, wherein the amount of nitrogen-sulfur co-doped carbon dot added to the lubricating oil is 0.05-5 wt%.
[0038] In one specific embodiment, the lubricating oil is one of PEG, PAO, and PAG.
[0039] Compared to pure PEG200, a concentration of only 0.1 wt% can reduce the average coefficient of friction from 0.245 to 0.128, a reduction of 56%. Wear volume can be reduced by 59%.
[0040] The following specific examples will provide further explanation.
[0041] Example 1
[0042] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0043] S1. Dissolve 0.3g of trinitropyrene and 0.9g of thiourea in 50mL of ultrapure water, add 15mL of ammonium hydroxide solution, and ultrasonically disperse in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour into a 100mL hydrothermal reactor and hydrothermally treat at 200℃ for 10h. Cool to obtain the precursor.
[0044] S2. Add 65 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0045] Example 2
[0046] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0047] S1. Dissolve 0.3g of trinitropyrene, 0.9g of thiourea and 1.5g of guanidinopropionic acid in 60mL of ultrapure water, and ultrasonically disperse them in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour the solution into a 100mL hydrothermal reactor and hydrothermally treat it at 200℃ for 12h. Cool to obtain the precursor.
[0048] S2. Add 60 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0049] Example 3
[0050] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0051] S1. Dissolve 0.3g of trinitropyrene, 0.9g of thiourea and 1.7g of glutamic acid in 70mL of ultrapure water, and ultrasonically disperse them in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour the mixture into a 100mL hydrothermal reactor and hydrothermally treat it at 200℃ for 8h. Cool to obtain the precursor.
[0052] S2. Add 70 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0053] Example 4
[0054] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0055] S1. Dissolve 0.3g of trinitropyrene, 0.9g of thiourea and 1.8g of histidine in 50mL of ultrapure water, and ultrasonically disperse them in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour the mixture into a 100mL hydrothermal reactor and hydrothermally treat it at 200℃ for 10h. Cool to obtain the precursor.
[0056] S2. Add 60 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0057] Example 5
[0058] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0059] S1. Dissolve 0.3g of trinitropyrene and 0.7g of thiourea in 50mL of ultrapure water, add 15mL of ammonium hydroxide solution, and ultrasonically disperse in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour into a 100mL hydrothermal reactor and hydrothermally treat at 200℃ for 10h. Cool to obtain the precursor.
[0060] S2. Add 65 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0061] Example 6
[0062] A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive includes the following steps:
[0063] S1. Dissolve 0.3g of trinitropyrene and 0.5g of thiourea in 50mL of ultrapure water, add 15mL of ammonium hydroxide solution, and ultrasonically disperse in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour into a 100mL hydrothermal reactor and hydrothermally treat at 200℃ for 10h. Cool to obtain the precursor.
[0064] S2. Add 65 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-sulfur co-doped carbon dot lubricating oil additive, named N,S@CDs.
[0065] Comparative Example 1
[0066] A method for preparing a nitrogen-doped carbon dot lubricating additive includes the following steps:
[0067] S1. Dissolve 0.3g of trinitropyrene and 1.5g of guanidinopropionic acid in 50mL of ultrapure water, and ultrasonically disperse them in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour them into a 100mL hydrothermal reactor and hydrothermally treat them at 200℃ for 10h. Cool to obtain the precursor.
[0068] S2. Add 65 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-doped carbon dot lubricating oil additive, named N@CDs.
[0069] Comparative Example 2
[0070] A method for preparing a sulfur-doped carbon dot lubricating additive includes the following steps:
[0071] S1. Dissolve 0.3g of trinitropyrene and 0.9g of thiourea in 50mL of ultrapure water, and ultrasonically disperse them in a constant temperature water bath at 10-30℃ for 1h. After ultrasonic treatment, pour the mixture into a 100mL hydrothermal reactor and hydrothermally treat it at 200℃ for 10h. Cool to obtain the precursor.
[0072] S2. Add 65 mL of methanol to the precursor and mix thoroughly at room temperature. After mixing at room temperature, filter the mixture using a 0.22 μm microporous aqueous filter membrane. Dialyze the filtrate for 2 days using a dialysis bag with a molecular weight cutoff of 1000 Da. Freeze-dry the filtrate to obtain an amino-passivated nitrogen-doped carbon dot lubricating oil additive, named S@CDs.
[0073] Figure 1 The image shows the transmission electron microscope (TEM) morphology of the N,S@CDs prepared in Example 1 of this invention. Figure 1 In the image, a is a transmission electron microscope (TEM) morphology image, and b is a high-resolution TEM lattice image. For example... Figure 1 As shown in the transmission electron microscope (TEM) image a, the size of the prepared N,S@CDs is concentrated around 3.8 nm. The high-resolution image with aberration correction clearly shows that the lattice spacing of 0.21 nm corresponds to the (100) crystal plane of graphene. The resulting zero-dimensional nanostructure is almost defect-free and highly crystalline with a diameter of <5 nm.
[0074] 1 mg of N,S@CDs prepared in Example 1, 1 mg of N@CDs prepared in Comparative Example 1, and 1 mg of N,S@CDs prepared in Comparative Example 2 were dispersed in 999 mg of PEG200 base oil and shaken thoroughly to obtain nitrogen-sulfur co-doped carbon point lubricants for performance testing.
[0075] Figure 2 The N,S@CDs prepared in Example 1, Comparative Example 1, and Comparative Example 2 were added to PEG200 at a concentration of 0.1 wt% to obtain the friction coefficient curves and wear characteristics of the doped carbon dot lubricants. Figure 2 In the diagram, a represents the friction coefficient curves of various doped carbon dot lubricants, and b represents the surface morphology of the wear scars after lubrication with various doped carbon dot lubricants and after lubrication with pure PEG200. For example... Figure 2 As shown in Figure a, the average friction coefficient of the nitrogen-doped carbon dot lubricant prepared with PEG200 is reduced by 30%, and the average friction coefficient of the nitrogen-sulfur co-doped carbon dot lubricant prepared with PEG200 is reduced by 48%. Figure 2 As shown in Figure b, the PEG200 wear surface has obvious scratches and furrows. After lubrication with nitrogen-sulfur co-doped carbon point lubricant, the furrows disappear, the scratches are greatly reduced, and the wear surface becomes smooth.
[0076] Figure 3 The images show the dispersion stability of N@CDs prepared in Example 1 of this invention, N@CDs prepared in Comparative Example 1, and S@CDs prepared in Comparative Example 2 in PEG200, along with a comparison of their tribological properties before and after placement. Figure 3 In the image, a shows photographs of N,S@CDs dispersed in PEG200 at different storage times (5 months); b shows the particle size distribution of N,S@CDs in PEG200 after 5 months; and c shows a comparison of the tribological properties of freshly prepared N,S@CDs and N,S@CDs after 5 months of storage. Figure 3 As shown, the prepared nitrogen-sulfur co-doped carbon point lubricant can maintain dispersion stability for a long time without agglomeration within 5 months, and the average friction coefficient only increases by 1.6% after standing for 5 months.
[0077] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
[0078] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing a nitrogen-sulfur co-doped carbon dot lubricating additive, characterized in that, Includes the following steps: Trinitropyrene and thiourea were dissolved in water, and amine was added to form a mixed solution. The solution was then ultrasonically dispersed in a constant temperature water bath. After ultrasonic treatment, the precursor was obtained by hydrothermal treatment at 160~250℃. In the mixed solution, the concentration of trinitropyrene is 1.0~8.0 g / L, and the concentration of thiourea is 0.1~1.0 M; When the amine is ammonium hydroxide, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 1.0~2.0 M; when the amine is one of guanidinopropionic acid, glutamic acid, histidine and its derivatives, the concentration of the amine in the mixed solution of trinitropyrene and thiourea is 0.1~0.3 M. An organic solvent was added to the precursor, and after mixing at room temperature, the mixture was filtered, dialyzed, and dried to obtain a nitrogen-sulfur co-doped carbon dot lubricating oil additive.
2. The preparation method of the nitrogen-sulfur co-doped carbon dot lubricating additive according to claim 1, characterized in that, The temperature of the constant temperature water bath is 10~30℃, and the ultrasonic dispersion time is 1~2 h.
3. The preparation method of the nitrogen-sulfur co-doped carbon dot lubricating additive according to claim 1, characterized in that, The hydrothermal treatment time is 6~18 h.
4. The preparation method of the nitrogen-sulfur co-doped carbon dot lubricating additive according to claim 1, characterized in that, The volume ratio of the precursor to the organic solvent is 1:1, and the organic solvent is one of ethanol, methanol, and ethylene glycol.
5. The preparation method of the nitrogen-sulfur co-doped carbon dot lubricating additive according to claim 1, characterized in that, The filtration membrane used was a 0.22 μm aqueous microporous membrane, and the dialysis bag used had a molecular weight cutoff of 500~3500 Da. The dialysis time was 1~2 days.
6. A nitrogen-sulfur co-doped carbon dot lubricant additive prepared by the preparation method according to any one of claims 1-5.
7. The application of the nitrogen-sulfur co-doped carbon dot lubricating oil additive according to claim 6 in lubricating oil, characterized in that, The amount of nitrogen-sulfur co-doped carbon dots added to the lubricating oil is 0.05~5wt%.
8. The application according to claim 7, characterized in that, The lubricating oil is one of PEG, PAO, or PAG.
Citation Information
Patent Citations
Organic carbon nanosphere lubricating oil additive and preparation method and application thereof
CN110317659A
Nitrogen doped graphene quantum dots as well as preparation method and application thereof
CN110499155A
Formulation for the synthesis of thermal nanofluid based on carbon nanodots
US20190367368A1